Faecal microbiota transplantation for patients with diabetes type 1 and severe gastrointestinal neuropathy (FADIGAS): a randomised, double-blinded, placebo-controlled trialResearch in context - Katrine Lundby Høyer; Simon Mark Dahl Baunwall; Ditte Smed Kornum; Mette Winther Klinge; Asbjørn Mohr Drewes; Knud Bonnet Yderstræde; Louise Bruun Thingholm; Martin Steen Mortensen; Susan Mikkelsen; Christian Erikstrup; Christian Lodberg Hvas; Klaus Krogh (EClinicalMedicine)
Summary: Background: Diabetic gastroenteropathy is associated with nausea, vomiting, bloating, pain, constipation, and diarrhoea. Current therapies are scarce. We tested faecal microbiota transplantation (FMT) for patients with type 1 diabetes and gastroenteropathy. Methods: In a randomised, double-blinded, placebo-controlled pilot trial, adults with type 1 diabetes and moderate-to-severe gastrointestinal symptoms were randomised (1:1) to encapsulated FMT or placebo. Each patient received around 25 capsules containing 50 g of faeces, administered in a single dose. The placebo capsules contained glycerol, saline and food colouring. All patients received FMT as a second intervention. The primary endpoint was number of adverse events of severity grade 2 or more assessed by the Common Terminology Criteria for Adverse Events during the week following the first intervention. Secondary endpoints included gastrointestinal symptoms and quality of life assessed four weeks after treatment. Public trial registration, ClinicalTrials.gov NCT04749030. Findings: We randomised 20 patients to FMT or placebo. Following this intervention, 26 adverse events of grade 2 or more occurred. Four patients in the FMT group reported seven adverse events, and five patients in the placebo group reported 19, with no differences between the groups. The most frequent adverse events were diarrhoea, bloating, and abdominal pain. No serious adverse events were related to the treatment. Patients who received FMT reduced their median Gastrointestinal Symptom Rating Scale—Irritable Bowel Syndrome score from 58 (IQR 54–65) to 35 (32–48), whereas patients receiving placebo reduced their score from 64 (55–70) to 56 (50–77) (p = 0.01). The Irritable Bowel Syndrome Impact Scale score improved from 108 (101–123) to 140 (124–161) with FMT and 77 (53–129) to 92 (54–142) with placebo (p = 0.02). The Patient Assessment of Gastrointestinal Symptom Severity Index declined from a median of 42 (28–47) to 25 (14–31) after FMT and 47 (31–69) to 41 (36–64) after placebo (p = 0.03). Interpretation: FMT was safe and improved clinical outcomes for patients with type 1 diabetes suffering from bowel symptoms. Funding: Steno Collaborative Grant.